IOT EFFECTIVENESS IN SUPPORTING ACADEMIC WORK AND ENHANCING LEARNING EXPERIENCES - Sardaran Leghari; Rabia; Rabella Abro; Asadullah Burdi; Jamil Ahmed (Spectrum of Engineering Sciences, 2025)
This paper aims to examine students' perceptions concerning the effectiveness of IoT in the form of academic work support from the use of IoT tools and the improvement of learning in the context of higher education. A cross-sectional research approach was employed and quantitative data were gathered using a structured questionnaire administered among undergraduate students at the University of Sindh, Jamshoro, Pakistan. The questionnaire measured dimensions such as characteristics of the task, characteristics of the technology, task-technology fit, and the effect of the technology on performance. Descriptive statistics were used to analyze data. The results showed students generally perceive that the use of IoT facilitates education tasks efficiently, such as real-time access to information, enhancing classroom interactions, and the ability to deliver personalized studies. Concern with data protection, technical issues, and unreliable access to IoT facilities across institutions was also noted. In connection with the findings, the study recommends strategic alignment of IoT with academic tasks, investment in digital infrastructure, and capacity building through awareness and training for effective and secure adoption in higher education.